2019
DOI: 10.24940/theijhss/2019/v7/i5/hs1905-050
|View full text |Cite
|
Sign up to set email alerts
|

Diglossia in Arabic: Views and Opinions

Abstract: is a compound Greek word in which di means two and glôssa means tongue or language,(Merriam-Webster Dictionary, n.d.).It means that there are two forms of the language used for different situations. According to Oxford Dictionary, diglossia is a situation in which two languages (or two varieties of the same language) are used under different conditions within a community, often by the same speakers, (English Oxford Living Dictionaries, n.d.) Another definition is listed on Wikipedia as a situation in which two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Although as we previously mentioned, this definition of WA generally relates to supra-national contexts, our data also points at two specific national contexts where the term WA also aligns with the present definition: Jordan and Yemen. WA is listed by Alfaisal & Aljanada (2019) as one of the dialects of Jordan, which is used when speakers of «considerably different» varieties spoken in Jordan communicate with each other (Alfaisal & Aljanada, 2019, p. 110). The same is claimed about Yemen, where Dufour (2008) observed that WA is used when mutual understanding is endangered by the perceived linguistic distance between local Yemeni dialects (Dufour, 2008, p. 141).…”
Section: Arabic Original: [Al-lahǧatu Al-bayḍāɂu ɂAw L-luġatu L-bayḍā...mentioning
confidence: 99%
“…Although as we previously mentioned, this definition of WA generally relates to supra-national contexts, our data also points at two specific national contexts where the term WA also aligns with the present definition: Jordan and Yemen. WA is listed by Alfaisal & Aljanada (2019) as one of the dialects of Jordan, which is used when speakers of «considerably different» varieties spoken in Jordan communicate with each other (Alfaisal & Aljanada, 2019, p. 110). The same is claimed about Yemen, where Dufour (2008) observed that WA is used when mutual understanding is endangered by the perceived linguistic distance between local Yemeni dialects (Dufour, 2008, p. 141).…”
Section: Arabic Original: [Al-lahǧatu Al-bayḍāɂu ɂAw L-luġatu L-bayḍā...mentioning
confidence: 99%
“…Moreover, Gharawi and Bidin (2016) and Batainah, Din, and Al Mashakbh (2018) scrutinized computeraided and hybrid ASL learning aspects and teaching and learning issues ASL, respectively. Likewise, O'Sullivan (2017), Zakaria, Atan, and Robe'ah-Yusuf (2019) and Jwaifell, Abu-Omar, and Al-Tarawneh (2018) focused on the professional development of trainer aspects of ASL pedagogy based on innovative and technology-based interventions while Carroll et al (2017), Shendy (2019), Alfaisal and Aljanada (2019) and Saiegh-Haddad and Ghawi-Dakwar (2017) technology integration or diffusion barriers. Similarly, Haron, Ahmed, Mamat, Ahmad, and Rawash (2016) and Kennetz and Carroll (2018) examined multimedia software's efficacy in teaching ASL based on computer-assisted programs.…”
Section: Synthesis Of Key Concepts and Theoretical Conceptsmentioning
confidence: 99%